Exercise-with-melatonin therapy improves sleep disorder and motor dysfunction in a rat model of ischemic stroke - Haitao Zhao; Tong Zhang; Haojie Zhang; Yunlei Wang; Lingna Cheng (Neural Regeneration Research, 2024)
[INLINE:1] Exercise-with-melatonin therapy has complementary and synergistic effects on spinal cord injury and Alzheimer’s disease, but its effect on stroke is still poorly understood. In this study, we established a rat model of ischemic stroke by occluding the middle cerebral artery for 60 minutes. We treated the rats with exercise and melatonin therapy for 7 consecutive days. Results showed that exercise-with-melatonin therapy significantly prolonged sleep duration in the model rats, increased delta power values, and regularized delta power rhythm. Additionally, exercise-with-melatonin therapy improved coordination, endurance, and grip strength, as well as learning and memory abilities. At the same time, it led to higher hippocampal CA1 neuron activity and postsynaptic density thickness and lower expression of glutamate receptor 2 than did exercise or melatonin therapy alone. These findings suggest that exercise-with-melatonin therapy can alleviate sleep disorder and motor dysfunction by increasing glutamate receptor 2 protein expression and regulating hippocampal CA1 synaptic plasticity.